Klasifikasi Umur Padi berdasarkan Data Sensor Warna dengan menggunakan Metode K-NN - Anggi Diatma Styandi; Dahnial Syauqy; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesian country is one of the rice producers. Most of Indonesian people work in agriculture. However, it is unfortunately that Indonesia cannot meet the national rice needs so that supposes Indonesia to import rice from other countries. The cultivating time of farmers in Indonesia is still one of the causes lack of rice quality and quantity that is less than optimal, so that the quality of rice products is still said to be deficient. Rice that is cropped too late has very bad impacts. Therefore, farmers should be smart in choosing the right time to crop rice. Weather factors and large fields make it increasingly difficult for farmers to check the age of their whole rice regularly. Based on these problems, farmers now need a system to help observing the age of rice by seeing on changes in the color of rice plant so that the study entitled